Menelisik Corak Khas Penafsiran Nusantara (Studi Kasus Tafsir Mara>h Labi>d Karya Syaikh Nawawi al-Bantani) - Ida Mufidah; Muhammad Fathoni Hasyim (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2021)
The archipelago has a lot of ‘ulama’ with a distinctive scientific understanding, including in the field of interpretation. One of the scholars of the archipelago whose knowledge is recognized by the world in the field of interpretation is Shaykh Nawawi Al-Bantani. His work, the book Marah Labi>d, has a distinctive Indonesian style in peeling and interpreting the contents of the verses of the Qur’an. This paper seeks to examine the distinctive features of the interpretation of the archipelago in the book by using the literature study method. From the results of the research conducted, it can be concluded that Tafsi>r Mara>h Labi>d combines the use of ijma>li (global) and tahlili> (analysis) interpretation methods at the same time. Where Shaykh Nawawi at the beginning of the discussion interprets as briefly as possible the contents of the new verse or letter then interprets it in detail starting from the description of the meaning of vocabulary, muna>sabah, asba>b nuzul, variety of qira’a>t, to related narrations. Shaykh Nawawi also uses the muqa>ranah (comparative) method when interpreting the ahka>m verse by expressing differences in the opinions of the ulama’ and comparing them without fanaticism and criticism of schools that are different from the Shafi’i school that he adheres to. In addition, Shaykh Nawawi also combines tafsi>r bi al-ma’tsu>r with tafsi>r bi al-ra’y al-mahmu>d in the Mara>h Labi>d book.